Penerapan Metode Kooperatif Tipe Stad Untuk Meningkatkan Prestasi Belajar Pendidikan Kewarganegaraan Pada Siswa Kelas XI IPS 1 SMA Negeri 1 Malaka Barat Tahun Pelajaran 2022/2023 - Marselina Fahik (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This academic study aims to improve the learning quality of class XI IPS 1 students for the 2022/2023 academic year. In addition, it is to find out whether cooperative learning using the STAD method can improve Pkn learning achievement for class XI IPS 1 students in the 2022/2023 academic year. The teacher provides a good, fun, and stimulating learning environment so that students can think and develop according to their needs. Cooperative learning encourages students to work together to achieve goals. It is interesting to observe the extent and understanding of students in class XI IPS 1 about Civics after the STAD-type cooperative learning method was implemented in the 2022-2023 school year. Academic achievement is the final result of learning, which can be measured by the grades or scores achieved by students at the end of a given course. This research involved 36 enthusiastic students of class XI IPS 1. The use of observation sheets and test questions can facilitate data collection. The results showed that student participation in cycle II increased to 75.28, a significant value when compared to the value of cycle I 69.03. It is very encouraging to see an increase in student learning outcomes from 61.11% to 86.11% between cycles I and II. The results showed that STAD group learning increased the academic achievement of class XI IPS 1 SMA Negeri 1 West Malaka.